Lifestyle from Scientist’s Perspective (Simmel, Weber and Bourdieu) (Theoretical Study) - Abdullah Kurshid Abdullah; Shahlaa Wali Jabbar (QALAAI ZANIST JOURNAL, 2020)
Lifestyle, which results some cultural, social political and psychological outcomes, has brought scientific attention of various majors. This theoretical study aims to discuss the different aspects of lifestyle from sociology point of view particularly from Simmel, Weber and bourdieu's perspectives. Besides, it tries to trace the origin of the concept historically and how reflect in thought of the three mentioned sociologists to applied in their study. It can be said that the obvious changes in modern aeria comes from consumption, so we need a new conceptual view to understand how these changes happened. It seems like lifestyle is one important term that helps us to deepen our perceive in societal phenomena that are affected by it. Through going to literature review the study summarizes that in which area this subject has been applied. In term of methodology the study is an analytical, because there are few studies that focus on dimension of lifestyle and date which related to this matter is not available, therefore, the researcher could be able to explain this matter theoretically to open the way to other researchers who interested in study lifestyle. This study also covers the relation between social class and status with lifestyle and how accordingly it differentiates the social identity of people who have a certain lifestyle, additionally, to what extend it generate social difference between them.